Learning from the internship: Integrating Japanese corporate needs with the curriculum design of the Japanese Study Program - Akhmad Saifudin; Bayu Aryanto; Fira Adelia Putri Febriyawati; Deny Kristiadi; Jeminika Isyamy Esika (Universitas Dian Nuswantoro, 2026)
This study examines how empirical data derived from internship programs in Japan can be systematically utilized to integrate Japanese corporate needs into the curriculum design of Japanese Studies programs in Indonesia. Employing a qualitative descriptive approach with an exploratory orientation, the research involved field monitoring, semi-structured interviews with Japanese host company representatives, Indonesian internship students, and intermediary agencies (kumiai), as well as document analysis of internship evaluations and curriculum materials. The findings reveal that Japanese companies prioritize competencies beyond linguistic proficiency, particularly professionalism and work ethics, workplace cultural literacy, strategic communication skills, and psychosocial readiness. The study further identifies a significant mismatch between language-oriented curricula and the multidimensional competencies required in Japanese workplace contexts. Through thematic analysis, four core competency domains were formulated: professionalism and work ethics, workplace cultural literacy, strategic communication, and mental readiness and adaptability. These competencies constitute the empirical basis for an industry-integrated curriculum model that positions internship programs not merely as experiential learning activities but also as continuous feedback mechanisms for curriculum development. The novelty of this study lies in its institutional and curriculum-oriented reconceptualization of internship programs by integrating industry expectations, student experiences, and intermediary agency perspectives into a unified curriculum framework. The findings contribute to studies on work-integrated learning and curriculum internationalization and provide practical implications for Japanese Studies programs seeking to align academic preparation with global workplace demands.